Dynamic analysis of vehicle–track interaction due to wheel flat using bond graph. (September 2018) - Kumar, Vivek; Rastogi, Vikas; Pathak, PM
The dynamic response of a railway track under a moving train in the presence of a wheel with flat has been studied over many years. The force at the wheel–rail interface is mainly responsible for vehicle and track components deterioration and adds to the maintenance cost. So, reliable predictions of wheel–rail interaction forces are of prime concern to get the key factors responsible for damage of vehicle and track components. In most of the studies, a symmetrical vehicle–track model with linearity in track components behavior is assumed for simplification. This may lead to incorrect results in some situation. In this paper, wheel–rail impact dynamics is investigated by considering an asymmetrical vehicle–track model with due consideration to nonlinear behavior of track. Some nonlinear factors such as loss of wheel–rail contact, nonlinearity in pad, and ballast behavior are taken into consideration. A combined vehicle–track bond graph model is developed to study the wheel–track interaction dynamics. The rail is modeled as a flexible Euler Bernoulli beam resting on discrete support. The nonlinear Hertzian contact theory is used to accomplish the dynamic interactions between the vehicle and the track. Time response of forces, displacements, velocities, and accelerations of the related components of the vehicle and the track are obtained. It has been found that, though the wheel flat exists on leading right wheels, its effect has also been transferred to other components of the vehicle. The obtained results further lead to provide a better understanding of the interaction dynamics at the wheel–track interface with attention to the nonlinear behavior of pad and ballast.